Avaliação de um curso on-line sobre tuberculose na perspectiva de estudantes e profissionais de enfermagem - Ávila, Thaís Tânia (2020)
Tuberculosis is a disease that affects thousands of people worldwide, being an important public health problem, health workers must be prepared for the identification, diagnosis and treatment of those affected by tuberculosis. For such preparation, Permanent Health Education is a continuous education strategy, in order to improve knowledge, in the search for integral health and a link with the assisted community. Objective: The general objective of this study is to analyze the opinion of nursing students and professionals of Primary Health Care about a training course in tuberculosis, in the environment of the Moodle platform. Materials and methods: The approach used in this study is qualitative, with descriptive and exploratory analysis, using the Focus Group technique for data collection with seven guiding questions. For data analysis, the Content Analysis technique was used. Results and discussion: Six nursing graduates and six primary health care professionals participated in the study, in different focus groups. Where it was found that the participants evaluated the course in several aspects in a positive way, in addition to the majority reporting that they seek updates with a view to technological innovations, especially with regard to distance education. Final Considerations: TB control strategies still lack an integral dimension of assistance, and for this, educational actions, namely permanent education, aimed at undergraduate and nursing professionals are essential, training through distance education has characteristics that allow access to new knowledge on an equal basis.